The Impact of Pollution on China Marine Fishery Culture: An Econometric Analysis of Heterogeneous Growth - Yuan, Bin; Yue, Fangzhou; Wang, Xueye; Xu, Hanxiao (Frontiers in Marine Science, 2021)
The damage caused by pollution is not equal across individuals within a given population, due to the differences in pollution level and coping ability. Identifying the different impacts of environmental pollution on agricultural economic growth and the source of the pollution is of great reference significance for realizing the organic integration of ecological protection and relative poverty alleviation. This study takes marine fishery culture as an example, with the cultured products data of 53 coastal cities in China from 1994 to 2018 and empirically captures the heterogeneous effects of environmental pollution on mariculture growth by constructing a theoretical analysis framework of heterogeneity in pollution damage. Results show that the deepening of marine environmental pollution will reduce the growth rate of marine cultured output, emerging significant regional differences. Nevertheless, under the background of the complex environmental situation currently, further damages mainly derive from the difference in the ability to deal with environmental pollution rather than the difference in pollution degree. In terms of different wastewater sources, the impact of industrial wastewater discharge on marine aquaculture production is not very significant. In contrast, the adverse shocks of urban domestic sewage are more prominent. Notably, the environmental pollution has a significant cumulative effect, which is not reversed. Therefore, a pollution shock in one period may leave the region permanently further behind. Based on this, in the follow-up process of pollution control, we should fully consider the heterogeneity in coping ability of individuals. While promoting industrial wastewater emission reduction, we should emphasize strengthening of the urban domestic sewage treatment strategies and give overall consideration to the ecological environment treatment and regional coordinated development.